Problems of Legal Certainty in the Use of Artificial Intelligence in Business Practices - Rianthi, Nyoman Desy; Kurniawan, I Gede Agus (International Journal of Law Reconstruction, 2025)
The use of Artificial Intelligence (AI) in business brings many benefits, such as increased efficiency and innovation, but also presents challenges related to legal certainty, which has not yet been comprehensively regulated in Indonesia. This research aims to analyze the legal certainty of AI use in business practices in Indonesia based on SE Menkominfo 9/2023, and to evaluate the implications of the unclear regulations in the circular on AI implementation in Indonesia's business sector. This research uses normative legal methods with a legislative and conceptual approach through literature studies and descriptive-analytical qualitative analysis of primary, secondary, and tertiary legal materials. The research findings indicate that the regulatory framework for AI implementation in Indonesian business practices. While the circular provides basic guidelines for data protection and mandates compliance with Personal Data Protection Law, it fails to comprehensively address crucial aspects such as legal liability for AI-related errors, industry-specific regulations for sectors like banking and finance, and clear ethical guidelines for AI implementation. These regulatory gaps create multiple implications, including business uncertainty, potential innovation barriers, increased risks of AI misuse, challenges in personal data protection, complications in legal enforcement, and obstacles for multinational companies operating in Indonesia.